A Sustainability Agenda for Tropical Marine Science. Issue 1 (27th February 2017) - Partelow, Stefan; Schlüter, Achim; von Wehrden, Henrik; Jänig, Manuel; Senff, Paula
Abstract: Tropical coasts face unprecedented sustainability challenges for advancing human welfare and maintaining ecosystem functioning and diversity. These coupled social–ecological processes exist within interdependent relationships across multiple levels and scales. Reflection is needed on the knowledge tropical marine science generates to advance a research agenda for sustainability. In this article we systematically review 753 social and natural science articles conducted within the tropical coastal marine sector. Our results are organized in five themes. (1) The spatial distribution and disciplinary composition of research is not homogeneous across regions. (2) A third of all research lacks a stated problem orientation and coral reefs dominate the ecosystem focus. (3) Research is primarily conducted on selected subgroups of levels and scales. (4) The social and natural sciences focus on a varying diversity of system processes that indicate different degrees of inter‐ and intradisciplinary research. (5) Statistically clustered terminology usage across all articles indicates that distinct research communities exist across a social to natural science gradient. The social and natural sciences generate different types of knowledge associated with terminology at different scales. This analysis attempts to provide a guidepost for discussing the challenges and pathways forward to progress a sustainability agenda in tropical marine science.